Prognostic impact of pretransplant measurable residual disease assessed by peripheral blood WT1‐mRNA expression in patients with AML and MDS. (27th May 2021) - Rautenberg, Christina; Lauseker, Michael; Kaivers, Jennifer; Jäger, Paul; Fischermanns, Carolin; Pechtel, Sabrina; Haas, Rainer; Kobbe, Guido; Germing, Ulrich; Schroeder, Thomas
Abstract: Objective: As peripheral blood (PB) Wilm's Tumor 1 ( WT1 )‐mRNA expression is established as MRD‐marker during conventional AML chemotherapy, impact of pretransplant WT1 expression remains unclear. Therefore, we aimed to assess prognostic impact of pretransplant WT1 expression on post‐transplant outcome in patients with AML/MDS. Methods: In 64 AML/MDS patients, pretransplant WT1 expression was retrospectively analyzed using a standardized assay offering high sensitivity, specificity, and a validated cut‐off. Patients were divided into three groups determined by pretransplant remission and WT1 expression. Post‐transplant outcome of these groups was compared regarding cumulative incidence of relapse (CIR), relapse‐free (RFS), and overall survival (OS). Results: Pretransplant forty‐six patients (72%) showed hematologic remission, including 21 (46%) MRD‐negative and 25 (54%) MRD‐positive patients indicated by WT1 expression, while 18 refractory patients (28%) showed active disease. Two‐year estimates of post‐transplant CIR, RFS, and OS were similar in MRD‐positive (61%, 37%, 54%) and refractory patients (70%, 26%, 56%), but significantly inferior compared with MRD‐negative patients (10%, 89%, 90%). After multivariable adjustment, pretransplant MRD negativity measured by WT1 expression retained its prognostic impact on CIR ( P  = .008), RFS ( P  = .005), and OS ( P  = .049). Conclusions: PB WT1 expression represents a useful method to estimate pretransplant MRD, which is highly predictable for post‐transplant outcome and may help improving peri‐transplant management in AML/MDS patients.